A Novel Natural Penetration Enhancer for Transdermal Drug Delivery: In Vitro/In Vivo Evaluation and Penetration Enhancement Mechanism - Nanxi Zhao; Jiale Hao; Yucong Zhao; Bingqian Zhao; Jiayu Lin; Jian Song; Manli Wang; Zheng Luo (Pharmaceutics)
Objectives: This study aimed to identify and develop a novel, safe, and effective transdermal penetration enhancer derived from the leaves of Perilla frutescens (L.) Britt, and to explore the underlying mechanisms of its penetration enhancement effects. Methods: To evaluate the safety profile of the penetration enhancer, both skin irritation tests and histopathological analyses were conducted. The transdermal enhancement capabilities of the penetration enhancer were assessed in vitro using five model drugs. Furthermore, to gain insights into the penetration enhancement mechanism of this novel penetration enhancer, a range of analytical methods were used, including a spectroscopic technique, differential scanning calorimetry, micro-optical techniques, and molecular docking simulations. Results: Perilla essential oil contained 93.70% perilla ketone (PEK), which exhibited a safety profile superior to that of azone. PEK significantly increased the cumulative skin permeation of all the model drugs (p < 0.05). PEK exhibited the most obvious impact on puerarin penetration, with quantitative enhancement ratios of 2.96 ± 0.07 and 3.39 ± 0.21 at concentrations of 3% and 5% (w/v), respectively. A strong correlation between the enhancement effect of PEK and the physicochemical properties of the drugs was observed. Mechanistic studies revealed that PEK facilitates drug distribution from the solution phase to the stratum corneum (SC). Conclusions: PEK, seldom discussed in former studies, was observed to show extensive penetration enhancement effects by inducing conformational changes in SC lipids and disrupting the tightly ordered bilayer arrangement of lipids. These findings highlight the potential of PEK as a promising and safe natural transdermal penetration enhancer.